S-Nitrosothiol Signals in the Enteric Nervous System: Lessons Learnt from Big Brother - Savidge, Tor (Frontiers in Neuroscience, 2011)
Nitric oxide (NO) is a functionally important neurotransmitter signaling molecule generated by mammalian and bacterial nitric oxide synthases (NOS), and by chemical conversion of dietary nitrite in the gastrointestinal (GI) tract. Neuronal nNOS is the most abundant isoenzyme in the enteric nervous system, and targeted deletion in transgenic mice has clearly demonstrated its importance in normal gut function. Enteric neuropathy is also often associated with abnormal NO production, for example in achalasia and diabetic gastroparesis. Not surprisingly therefore, aberrant nNOS activity is widely implicated in enteric disease, and represents a potential molecular target for therapeutic intervention. One physiological signalling mechanism of NO bioactivity is through chemical reaction with the heme centre of guanylyl cyclase, resulting in the conversion of cGMP from GTP. This second messenger nucleotide signal activates cGMP-dependent protein kinases, phosphodiesterases and ion channels, and is implicated in the neuronal control of GI function. However, few studies in the GI tract have fully related NO bioactivity with specific molecular targets of NO-derived signals. In the central nervous system (CNS), it is now increasingly appreciated that NO bioactivity is often actively transduced via S-nitrosothiol (SNO) signals rather than via activation of guanylyl cyclase. Moreover, aberrant S-nitrosylation of specific molecular targets is implicated in CNS pathology. S-nitrosylation refers to the posttranslational modification of a protein cysteine thiol by NO, forming an endogenous SNO. Because cysteine residues are often key regulators of protein function, S-nitrosylation represents a physiologically important signaling mechanism analogous to other posttranslational modifications, such as O-phosphorylation. This article provides an overview of how neurotransmitter NO is produced by nNOS as this represents the most prominent and well defined source of SNO production